Characterization of T-lymphocyte populations and selected cytokine expressions of chickens vaccinated with H5-recombinant fowl pox viruses co-expressing IL-15 gene - Nor Majid, Nadzreeq (2016)
Fowl pox virus (FPV) has been modified to express avian influenza virus (AIV) antigens since the late 1980s. A more advanced approach would be to co-express a novel host cytokine from such recombinants and characterize its immune response. In this study, previously constructed H5-recombinant Fowl pox viruses co-expressing host IL-15 (rFPV) was inoculated into specific-pathogen-free (SPF) chickens. T-lymphocyte populations and selected cytokine expression namely IL-15 and IL-18 of the vaccinated chickens were evaluated to add the relatively limited knowledge of chicken IL-15 cytokine gene compared to that of mammalian. It is hypothesized that vaccination with H5-recombinant Fowl pox viruses co-expressing IL-15 gene is able to show a higher population percentage of CD4+ and CD8+ T lymphocytes, and high IL-15 and IL-18 expressions, compared to H5-recombinant vaccines alone, in chickens. Prior to in vivo characterization, recombinant viruses were propagated in Chicken Embryonic Fibroblast (CEF) primary cell line. Stability of H5 gene from influenza strain A/Chicken/Malaysia/5858/2004 (1695 kb), and IL-15 (695 kb) gene integrations was confirmed by using Polymerase Chain Reaction (PCR) with specific primers after three passages. Propagations and plaque assays were done until desired titres of recombinant viruses were obtained. Parental (FP9 wild-type) and recombinant virus vaccines (105 PFU) were inoculated subcutaneously into one-day-old SPF chickens. The immunogenicity of the recombinant viruses was analyzed based on evaluation of T-lymphocytes cell population via flow cytometry, from Peripheral Blood Mononuclear Cell (PBMC) of 14 and 28-days-old vaccinated chickens. Chickens inoculated with rFPV/H5/IL-15 had a higher increased in CD4+ T cells population relative to rFPV/H5 in both time points. However, the result showed that rFPV/H5/IL-15 was not significant (P>0.05) in inducing CD8+ T cells. In general, the percentage of CD4+ and CD8+ lymphocytes cell population in chickens immunized with rFPV/H5/IL-15 were statistically higher compared to chickens immunized with rFPV/H5 and FP9 wild-type virus (P<0.05). Specific gene expressions of SPF chickens inoculated with rFPV were analyzed by quantitative real-time PCR (qRT-PCR), following extraction of spleen from 14-day-old SPF chickens at days 2, 4 and 6 post-infection. Two target genes chosen were IL-15 and IL-18 genes. The rFPV/H5/IL-15 group showed an increased level of IL-15 and IL-18 genes expression up to 2 and 3.5 folds, respectively, within 6 days post-vaccination, compared with other inoculated groups. rFPV/H5 group showed an increased level of IL-15 gene expression at day 2 and maintained at day 4 until day 6, while the IL-18 expression was decreasing within 6 days. Overall, the FP9 wild type group showed a low cytokine expression level as compared to the recombinant virus groups. While histopathology results showed successful vaccination of rFPV into chicken cells, weekly weighing suggested that inoculation with rFPV might not influence any weight changes. In summary, this study showed modulation immunogenicity of FP9 Wild Type, rFPV/H5, and rFPV/H5/IL-15, with rFPV/H5/IL-15 being the best vaccine candidate compared to others.